Biogas quality and nutrient remediation in palm oil mill effluent through Chlorella vulgaris cultivation using a photobioreactor - T. Handayani; I.N. Djarot; N. Widyastuti; F.D. Arianti; A. Rifai; A.I. Sitomurni; M.M.A. Nur; R.N. Dewi; N. Nuha; J. Haryanti; D. Pinardi; Y. Suryana; et al. (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: During this energy transition, research is being done to develop sustainable ways to support the shift to a decarbonized energy and production system. These ways include using renewable energy sources to promote circularity in products, green technologies, and safer procedures. Anaerobic digestion of palm oil mill effluent is a beneficial process for generating biogas, while the waste can also be utilized as fertilizer. The biogas can be further refined into biomethane, a valuable resource commonly used in transportation and power generation. The objective of this study is to examine the enhancement of biogas from Palm oil mill effluent and the elimination of sludge nutrients by utilizing microalgae Chlorella vulgaris. The microalgae will be cultivated in a modified photobioreactor to enhance the capture of carbon dioxide.METHODS: The study utilized anaerobic batch reactor digesters. A modified photobioreactor, consisting of two columns separated by a membrane, was developed for the technological advancement of biogas upgrading, specifically for carbon dioxide capture and biogas upgrading. A technological gap in biogas upgrade technology innovation is filled by the improved photobioreactor. To optimize the bio-fixation of carbon dioxide from flue gas, it is essential to carefully select a suitable strain of microalgae that possesses both a strong ability to absorb carbon dioxide and a high tolerance to varying concentrations of this gas. By choosing the right strain, the efficiency of carbon dioxide removal can be significantly enhanced. Since Chlorella vulgaris microalgae have demonstrated this potential, they were chosen for this investigation. Microalgae also play a role in removing nutrients contained in the sludge.  FINDINGS: Numerous chemical and biological methods have been used to upgrade biogas. Results of biological upgrading of biogas from palm oil mill effluent have been reported, with carbon dioxide removal reaching 89 percent until the methane concentration of the biogas is upgraded to 84 percent. The highest biomass of 1,835 grams per liter was achieved by culturing the microalgae Chlorella vulgaris in laboratory-scale photobioreactors. In this study, the application of 15 percent volume per volume biogas with an optical density of 0.4 was found to be optimal for the growth of the microalgae. The cultivation period lasted for 14 days. The peak biomass production was observed due to the achievement of a remarkable 98 volume per volume efficiency in carbon dioxide removal, which subsequently led to a significant rise in methane content, reaching 60 percent. The enhanced biogas achieved a peak methane content of 98 percent, indicating a significant improvement in quality.CONCLUSION: The findings of this study, conducted using a modified photobioreactor, indicate that Chlorella vulgaris demonstrated high efficacy in the removal of carbon dioxide, with a rate of up to 90 percent. Additionally, it exhibited remarkable performance in upgrading biogas derived from palm oil mill effluent, achieving a conversion rate of up to 98 percent. The optical density of microalgae at 0.4 played a crucial role in these processes. Furthermore, Chlorella vulgaris showcased its ability to effectively eliminate nutrient nitrogen, reaching a removal rate of 90 percent at an optical density of 0.2. Moreover, it demonstrated a phosphate removal rate of 80 percent at an optical density of 0.4.